A modified inverter topology for fault-tolerant direct torque control induction motor drive. Issue 12 (1st December 2020) - Gupta, Y. Bhaskar S. S.; Rao, S. Srinivasa
ABSTRACT: A modified fault-tolerant voltage source inverter-fed induction motor drive to maintain normal operation during open-circuit or short-circuit of power devices is proposed. The proposed inverter topology consists of a single capacitor at dc-link to eliminate the voltage-balancing issue in conventional fault-tolerant topology and a boost converter at the front end of inverter to operate the drive in full-rated condition during post-fault operation. Current control technique for boost converter and direct torque control for induction motor drive is implemented. The proposed topology reduces the stator current THD, torque and stator flux ripple when compared with the conventional fault-tolerant topology. Analysis of the proposed converter topology, modelling, simulation and experimental results are presented and also compared with the conventional fault-tolerant topology to highlight the eminence of the proposed scheme.